Perkembangan Gamification dan Dampak Game Online terhadap Jiwa Manusia di Kota Pintar DKI Jakarta - Nur Kumala Dewi; Arman Syah Putra (Jurnal Informatika Universitas Pamulang, 2020)
In this study, online games are a research problem that is raised, by raising all things in online games, the author wants to know the impact of online games that have been troubling society and the results of this study are suggestions that will make the basic ingredients of decision making in terms of online games has troubled all levels of society. This research method uses literature review and field review, with the two process methods used it will produce valid research, with research based on previous research, the research will be more renewable, and research carried out in the field will find out the problems in the field. There have been many studies discussing the effect of online games, and in this study discussing the impact on the human psyche. In this study, researchers took data from many parties who were deemed necessary, and made the basis of their research. This research will produce suggestions and proposals that will be applied in a smart city in making a policy in an online application that is troubling the public.